Video Killed the News Article? Comparing Multimodal Framing Effects in News Videos and Articles. Issue 4 (2nd October 2018) - Powell, Thomas E.; Boomgaarden, Hajo G.; De Swert, Knut; de Vreese, Claes H.
Abstract : The recent proliferation of online videos captured at the scene of news events begs the question: Do news videos have a meaningful impact on citizens' political opinions and behaviors that is different than that of news articles? This was examined in an experiment using carefully matched videos and articles about the European refugee crisis. Findings show that articles generated stronger intentions to help refugees than videos, and this was mediated by the depth with which the news story was processed. Despite their increasing prominence and intuitively impactful qualities, news videos do not deliver more powerful effects than news articles.